Air Pollution and Heat Impacts on Respiratory Morbidity and Mortality Outcomes in Africa: A Systematic Review Towards a Meta-analysis - Caradee Y Wright; Thandi Kapwata; Viwe Dikoko; Chantelle Howlett-Downing; Natasha Naidoo (Current Environmental Health Reports, 2026)
Abstract Purpose of the review This review synthesised evidence on associations between air pollution and respiratory morbidity in Africa. Following PRISMA guidelines, we systematically searched PubMed, ScienceDirect and Elicit for case-control studies published between 2015 and 2025. Recent findings Thirteen studies from ten African countries reported pollutant levels far exceeding WHO guidelines. Indoor PM₂.₅ in biomass-using homes ranged from 96 to 177 µg/m³, and ambient PM₂.₅ reached 259 µg/m³. Nitrogen oxides were consistently associated with reduced lung function in children, while household air pollution increased risks of under-five mortality and low birthweight. Associations with acute respiratory infections varied across settings. Vulnerability was greatest among young children, those with airway hyperresponsiveness, and households with poor ventilation. Only three studies included temperature, and none examined heat–respiratory interactions. Summary Across African case-control studies, particulate matter and household air pollution remain consistently linked to adverse respiratory outcomes, highlighting urgent needs for cleaner fuels, improved ventilation, and stronger evidence on combined pollution and heat exposures.